2013
DOI: 10.1039/c3nr00136a
|View full text |Cite
|
Sign up to set email alerts
|

Dual-donor (Zni and VO) mediated ferromagnetism in copper-doped ZnO micron-scale polycrystalline films: a thermally driven defect modulation process

Abstract: The paper reports robust ferromagnetic Cu-doped ZnO micron-scale polycrystalline films via spin-coating using high-quality doped nanocrystals. A reliable magnetic response is observed in the 900 °C vacuum annealed film without any ferromagnetic contribution from other sources. Post-annealing treatment in terms of atmosphere and temperature can control the proportion of oxygen vacancies (V(O)) and zinc interstitials (Zn(i)) defects and further help to precisely regulate defect-related ferromagnetic behavior. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 84 publications
3
44
0
Order By: Relevance
“…This result can be explained by the thermal displacement of donors on Zn sites by Zn i or via the formation of ionized donor -zinc interstitial defect pairs (D + -Zn i + ). [ 30 ] A Lorentzian line shape was used to fi t the g = 1.96 EPR peaks shown in Figure 2 a to compare their full width half maximum (FWHM). Figure 2 b shows the fi tted EPR spectra, which shows the FWHM decreasing from 9.5 to ≈6.8 G after annealing.…”
Section: Introductionmentioning
confidence: 99%
“…This result can be explained by the thermal displacement of donors on Zn sites by Zn i or via the formation of ionized donor -zinc interstitial defect pairs (D + -Zn i + ). [ 30 ] A Lorentzian line shape was used to fi t the g = 1.96 EPR peaks shown in Figure 2 a to compare their full width half maximum (FWHM). Figure 2 b shows the fi tted EPR spectra, which shows the FWHM decreasing from 9.5 to ≈6.8 G after annealing.…”
Section: Introductionmentioning
confidence: 99%
“…BMP concentration might be low due to the lower concentration of doped ions. Also a charge transfer processes derived from dualdonor (Zn i and O V ) might contribute partly in the FM interaction via indirect double-exchange mechanisms as proposed by Liang et al [17]. Also defect related surface spins from large surface area might contribute partly for the observed FM in the Co doped ZnO NPs as both sharp and broad defect modes have been seen in the PL spectra [33].…”
Section: Possible Fm Interactionmentioning
confidence: 93%
“…[39] to realize possible origin of RT FM and talked about hole-mediated exchange interactions where a curie temperature above room temperature in p-type ZnO with 5% Mn ions as dopants and a carrier concentration of 3.5 Â 10 20 holes cm À3 have been predicted [1]. Also different groups have demonstrated that the FM state might be stabilized by additional electron or hole doping in case of TM doped ZnO [17,40]. The presence of intrinsic defects (O V, Zn i , Zn V etc.)…”
Section: Possible Fm Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its Curie temperature (T c ) was theoretically predicted to be above room temperature [9], TMdoped ZnO has been extensively studied and room temperature ferromagnetism (RTFM) has been experimentally observed in Co-, Mn-, Cu-doped ZnO system [10]. Among them, Cu-doped ZnO nanostructures, easy to optically chase defect structure [11,12] and eliminated from secondary magnetic phase or clusters [13,14], have been most intensively investigated as a prototypical model to clary the origin of RTFM. If considering spin-orbit coupling, its moment can reach 3.55m B /atom [15], higher than that of Mn- [16], Co- [17] doped ZnO samples.…”
Section: Introductionmentioning
confidence: 99%